Pathways to prejudice and outgroup hostility: Group alignment and intergroup conflict among football fans - White, F; Newson, M; Verrelli, S; Whitehouse, H (Wiley, 2021)
How do different forms of group alignment influence our attitudes toward outgroups? To answer this, the current fieldwork study explored how identification and identity fusion differentially impact outgroup anxiety, prejudice, and hostility toward rival football fan supporter groups in Australia. The community participants (N = 100) were members of two active fan groups who had experienced a history of intergroup tensions. The findings from the full path model confirmed that the predictor group alignment variables of identification and fusion were correlated, and the two outcome variables of outgroup prejudice and hostility were correlated, as predicted. The findings also revealed that fusion with one's club predicted outgroup hostility, but not prejudice, whereas identification with one's club predicted outgroup prejudice, but not hostility. Additionally, outgroup anxiety was found to significantly mediate the relationship between ingroup identification and outgroup prejudice, whereas a similar relationship was not found for fusion. These findings highlight the differential impact of group alignment (i.e., identification and identity fusion) on social constructs of outgroup anxiety, prejudice, and hostility. Empirically, this is the first study to demonstrate the workings of these distinct group alignment pathways in an applied setting involving hard-core football fans. We discuss the broader implications of these findings for a fuller understanding of the drivers of intergroup tensions and conflict.